Competition for Savings Deposits in the U.S.: 1936-1966 - Spellman, Lewis J. (Journal of Financial and Quantitative Analysis, 1975)
The growing sensitivity of savings deposits to flow in response to changes in interest rate differentials has become so commonplace in the past decade that the term “disintermediation” has become a part of the economists' vocabulary. It is a major conclusion of this paper that the volatility of savings deposits began to increase as early as 1950 for savings and loan associations and credit unions and as early as 1945 for mutual savings banks. As an indication of this, we proxy changes in the competitive environment for savings deposits by making yearly estimates of the elasticity of savings deposits with respect to deposit rates at savings and loan associations, mutual savings banks, and credit unions.